S111 Does rate of decline in lung function predict response to Pirfenidone therapy in patients with Idiopathic Pulmonary Fibrosis?. (12th November 2015) - Eaden, JA; Barber, C; Bianchi, SM
Abstract : Introduction and objectives: Idiopathic pulmonary fibrosis (IPF) is a progressive, irreversible interstitial lung disease with a poor prognosis. Randomised, placebo-controlled clinical trials have shown that treatment of IPF patients with pirfenidone reduces disease progression. Published studies used incident forced vital capacity (FVC) values for study inclusion. Our objective was to determine whether the rate of decline in lung function predicts response to therapy. Methods: The clinical records of 68 patients with IPF who started pirfenidone treatment between June 2013 and March 2015 at a UK tertiary referral centre were reviewed. 34 patients had lung function sufficient for a full evaluation. Results: The mean (+/-SE) rate of decline in FVC per year pre-treatment was 196.0+/-66.1 ml versus 135.0+/-61.8 ml post treatment (p = 0.512). The decline in percent predicted FVC per year pre-treatment was 4.4+/-1.9% vs. 3.0+/-1.9% post treatment (p = 0.572). The decline in absolute total gas transfer (TLco) per year pre-treatment was 0.6+/-0.2 compared to 0.4+/-0.2 post treatment (p = 0.472). The decline in percent predicted TLco per year pre-treatment was 6.7+/-2.8% compared to 4.4 +/-2.0% post treatment (p = 0.504). Pirfenidone showed a trend towards positive benefit in all parameters measured. Patients were stratified into tertiles of slow, medium and rapid rate of FVC decline (pre-treatment). In slow and medium rate decliners (up to FVC decline of approximately 200 ml per year or 5.4% per year) no effect was seen (p = NS). In fast decliners (FVC decline 576.1+/-97.8 ml and FVC percent predicted decline 14.5+/-2.4% per year) a statistically significant effect was seen, reducing decline to 199.1+/-99.6 ml and 4.5+/-2.4% respectively (p = 0.022; 0.015). 16.2% of the patients died with a mean survival of 239 days post pirfenidone. Conclusions: Pirfenidone treatment reduced disease progression (decline in FVC and TLco) in our total cohort. Our results indicate that patients with rapid decline in FVC may benefit most from pirfenidone. Those declining at less than 200 ml per year may not benefit. These results suggest that further clinical studies are warranted, including patients with evidence of rapid lung function decline with FVC >80% predicted.